Os Passos da Paixão de Portinari da Igreja da Pampulha vistos através da história da arte técnica - Maria Tereza Dantas Moura (2022)
The Way of the Cross was painted by Candido Portinari (1903-1962) in 1945, to integrate the interior decoration of the São Francisco de Assis Church along with the artist's other six panels including tiles and frescoes. The church in its turn is part of the Pampulha Architectural Complex, designed by architect Oscar Niemeyer and engineer Joaquim Cardozo between 1942 and 1944. Given the great importance of the painter in Brazilian art, there is a vast bibliography on his biography and style, however, there are not enough references to the Way of the Cross, almost nothing is known about the techniques and material that was applied by the artist in his paintings and few studies were dealt with in the scope of the Technical Art History. The general aim of this work was to characterize the works of the Via-Sacra pointing out material, historical, aesthetic and cultural data, understanding the work as a material asset endowed with social meaning. Using the History of Technical Art as an approach methodology we present an interdisciplinary investigation of this set of paintings. The research is structured in three main axes: the historical, the aesthetic and the material which are interposed on the artistic objects analyzed through the gaze of the conservator-restorer who seeks to investigate these three instances of the works' characteristics aiming their understanding and conservation. We analyzed the extensive documentation on the Pampulha Church then we have found important records about the Passos which have their chronology since the works are movable and have taken part in exhibitions and restorations. The representations made by Portinari for these works portray characteristics that relate to the artistic moment lived by the painter and also to Niemeyer's architectural project which are very clear when compared to the Way of the Cross in Matriz de Batatais Church, painted by the artist in 1955. Scientific analysis revealed unprecedented and significant data on the construction technique of the works from the support to the most superficial layers also through the diagnosis of photographs with visible, grazing, ultraviolet and infrared light which pointed out data on the pictorial surface and the underlying drawings of the radiographs as well as a tomography which was fundamental to characterize the type of wood used in the panels and its state of conservation, and the physical-chemical examinations that made it possible to identify and/or indicate the composition of the pigments and fillers of the paints and preparation base. The interaction between the areas of knowledge proved to be satisfactory and enriching as methodology for artwork analysis, bringing consistent results and many possibilities for developments and research advance.